(untitled) (Faridpur Medical College Journal, 2015)
Eisenmenger syndrome (ES), the most advanced form of pulmonary arterial hypertension associated with congenital heart disease, is a devastating condition that has a considerable impact on patient’s life. Patients who develop ES typically exhibit one or more of a range of cardiac defects including ventricular septal defects (VSD), atrial septal defects (ASD) and patent ductus arteriosus (PDA). The nature of the congenital defect underlying ES is important because it has prognostic implications. Early diagnosis & treatment of cardiac defect before development of pulmonary hypertension is the key to definite management, otherwise only supportive management can be offered. Our patient Mr. Abdul Khaleque, 55 years old, businessman, non diabetic, non hypertensive admitted in DAMCH, cardiac unit with the complaints of shortness of breath on exertion since childhood, bluish discoloration of nails and toes for 10 years, headache and vertigo for 2 weeks. Initially it was during severe exertion and relieved by rest. Gradually the severity of breathlessness has increased. Now he has developed NYHA class III. He had history of repeated attacks of cough with expectoration of mucoid sputum with occasional scanty amount of blood which did not foul smell and did not change with posture. We diagnose him as Eisenmenger syndrome secondary to ASD and treat him with only medical measure. Faridpur Med. Coll. J. 2014;9(2): 105-107